Old Europe, new suburbanization? : governance, land, and infrastructure in European suburbanization - Phelps, N. A. (Nicholas A.) (Global suburbanisms., 2017)
"The youthful vigour of urbanization in North America has promulgated a dominant perspective on urban theory, specifically on suburbs, that establishes the United States as the norm against which all other contexts are measured. However, much of the vocabulary surrounding the American experience isn't applicable to the wider world. Old Europe, New Suburbanization? takes us on a journey of rediscovery into some of Europe's oldest metropolises. The volume's contributors reveal the great variety of patterns and processes of urbanization that make Europe a fruitful ground for furthering the diversity of global suburbanisms. The effects of urban history found in such cities as Athens, London, Madrid, Montpellier, and Sofia, varies greatly due to the sheer variety of economic, industrial, land, and expansionist policies at play on the continent. This collection highlights the varied historical and geographical manifestations that have shaped urban areas and provides evidence for new processes of suburbanization."--